Molecular Cloning, Sequencing and Expression of an Organic Solvent-Tolerant Lipase Gene from Bacillus Sphaericus 205Y - Chin, John Hun (2002)
Previously, a total of 131 organic solvent tolerant isolates originating from soil samples were successfully isolated via direct plating method using 1% (v/v) of either benzene, toluene, or a mixture of benzene and toluene as their sole carbon sources. Six out of these isolates demonstrated high tolerance of up to 75% (v/v) concentration of BTEX (benzene, toluene, ethyl benzene and xylene). These isolates were screened for lipolytic activity using triolein plates. Isolate 205y was found to produce the highest lipase yield in liquid medium and later identified as Bacillus sphaericus via 16S ribosomal DNA gene sequencing. In order to increase lipase yield, four production media were used and medium M3 yielded the highest lipase activity of 0.42 Umr⁻¹min⁻¹ at 36h incubation time. Stability studies in various organic solvents of 25% (v/v) for 30 min showed that lipase from B. sphaericus 205y was not only stable but also can be activated by hexane and xylene by 3.5 and 2.9 folds respectively. The activity, however, was greatly reduced in dimethyl sulfoxide and completely inactivated by hexadecane and acetonitrile. The gene coding for the extracellular lipase of Bacillus sphaericus 205y was isolated via genomic library and cloned into pUC 19.